2017
DOI: 10.1017/s0007114516004384
|View full text |Cite
|
Sign up to set email alerts
|

Collagen peptide ingestion alters lipid metabolism-related gene expression and the unfolded protein response in mouse liver

Abstract: Ingestion of collagen peptide (CP) elicits beneficial effects on the body, including improvement in blood lipid profiles, but the underlying mechanisms remain unclear. The purpose of this study was to investigate the effects of CP ingestion on the liver, which controls lipid metabolism in the body. Male BALB/cCrSlc mice were bred with the AIN-93M diet containing 14 % casein or the AIN-93M-based low-protein diet containing 10 % casein or a diet containing 6 % casein+4 % CP for 10 weeks (n 12/group). Total, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…However, 25(OH)D concentrations had a negative relationship with depression in some researches [ 52 ]. Ultraviolet B sunlight exposure, seasons, and diet were not considered [ 53 , 54 , 55 ], which largely affect the absorption of 25(OH)D.…”
Section: Discussionmentioning
confidence: 99%
“…However, 25(OH)D concentrations had a negative relationship with depression in some researches [ 52 ]. Ultraviolet B sunlight exposure, seasons, and diet were not considered [ 53 , 54 , 55 ], which largely affect the absorption of 25(OH)D.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of BAs, hepatic nuclear factor 4 alpha (HNF4α) downregulates Cyp8b1 transcription via upregulation of Shp [37]. Peroxisome proliferator activated receptor alpha (PPARα) is also a regulator of both Cyp7a1 and Cyp8b1 , and signaling from retinoic acid-related orphan receptor-α may additionally have a role in Cyp8b1 expression [38, 39]…”
Section: Enzymes Of the Classical And Alternative Bile Acid Synthesismentioning
confidence: 99%
“…Several studies to date have adopted different econometric approaches to deal with these issues. Courbage and Coulon used an instrumental variable (IV) approach to explore the effect of as one method for controlling the unobservable heterogeneity that jointly determines health insurance and health behavior [ 20 ]. Anderson used data from the U.S. Panel Study of Income Dynamics (1991–2003) to estimate a structural model and found that health insurance has significant incentive effects of unhealthy lifestyle choices, all of which have been shown by the medical literature to cause serious long-term health damage [ 21 ].…”
Section: Introductionmentioning
confidence: 99%